Employability Predictor Factors : Resilience, Self-Esteem, and Self-Confidence - Bella Rifqi Nabilah; Fatwa Tentama; Herlina Siwi Widiana (Psikostudia : Jurnal Psikologi, 2022)
This purpose of this study is to empirically examine the relationship between resilience, self-esteem, and self-confidence with employability. The researcher used class XI and XII students of private vocational schools in Kutawaluya as research subjects. The criteria that researchers set are students who have completed the industrial work practice program. The research sample consisted of 78 students of class XI and XII Business and Motorcycle Engineering, XI and XII Office Automation and Governance. Researchers obtained it by means of cluster random sampling technique. The measurement instrument that the researcher uses is the Likert model scale (employability scale, resilience scale, self-esteem scale, self-confidence scale) which the researcher compiled himself. The data analysis that the researcher uses is multiple linear regression with the SPSS V26 program. The results of the analysis show that simultaneously there is a very significant relationship between resilience, self-esteem, and self-confidence with employability (R = 0.884 and Sig. = 0.000). Based on these results, it can be concluded that the variables of resilience, self-esteem, and self-confidence can be predictors of high and low employability , so that the higher the resilience, self-esteem, and self-confidence of students, the higher the level of employability they have. Penelitian ini bertujuan untuk menguji secara empiris hubungan antara resiliensi, harga diri, dan kepercayaan diri dengan employability. Peneliti menggunakan siswa kelas XI dan XII SMK Swasta yang ada di Kutawaluya sebagai subjek penelitian. Kriteria yang peneliti tetapkan yaitu siswa-siswa yang telah menyelesaikan program praktek kerja industri. Sampel penelitian berjumlah 78 yang terdiri dari siswa kelas XI TBSM, XI OTKP, XII TBSM dan XII OTKP. Peneliti memperolehnya dengan cara teknik cluster random sampling. Instrumen pengukuran yang peneliti gunakan adalah skala model likert (skala employability, skala resiliensi, skala harga diri, skala kepercayaan diri) yang peneliti susun sendiri. Analisis data yang peneliti gunakan adalah regresi linier berganda dengan program SPSS V26. Hasil dari analisis menunjukkan bahwa secara simultan ada hubungan yang sangat signifikan antara resiliensi, harga diri, dan kepercayaan diri dengan employability (R = 0,884 dan Sig. = 0,000). Berdasarkan hasil tersebut dapat disimpulkan bahwa variabel resiliensi, harga diri, dan kepercayaan diri mampu menjadi prediktor dari tinggi rendahnya employability, sehingga semakin tinggi resiliensi, harga diri, dan kepercayaan diri siswa maka semakin tinggi juga tingkat employability yang dimilikinya.